Application of reverse osmosis in concentration of sugar solutions - A.M.A Elgaali (1981)
In this introduction attempts are made to give a brief idea about the sugar manufacturing process from sugar cane, the composition of cane juice and the evaporation process which is conventionally applied for the concentration of sugar solutions. Some disadvantages of the evaporation process will be highlighted...